In-situ mechanical behavior and slackness of the anterior cruciate ligament at multiple knee flexion angles. Issue 3 (March 2016) - Rachmat, H.H.; Janssen, D.; Verkerke, G.J.; Diercks, R.L.; Verdonschot, N.
Highlights: The tensile behavior and slackness of the anterior cruciate ligament was tested. The ACL slackness depended on flexion angle, and was highest at 75° and 90°. The ACL was stiffest at low and at high flexion angles. The current results contribute to tuning and validating knee models. Abstract: In this study the in-situ tensile behavior and slackness of the anterior cruciate ligament (ACL) was evaluated at various knee flexion angles. In four cadaveric knees the ACL was released at the tibial insertion, after which it was re-connected to a tensiometer. After pre-tensioning (10 N) the ACL in full-extension, the knee was flexed from 0° to 150° at 15° increments, during which the ACL tension was measured. At each angle the ACL was subsequently elongated and shortened under displacement control, while measuring the ACL tension. In this manner, the pre-tension or the slackness, and the mechanical response of the ACL were measured. All ACL's displayed a higher tension at low (0°–60°) and high (120°–150°) flexion angles. The ACL slackness depended on flexion angle, with the highest slackness found at 75°–90°. Additionally, the ACL stiffness also varied with flexion angle, with the ACL behaving stiffer at low and high flexion angels. In general, the ACL was stiffest at 150°, and most compliant at 90°. The results of this study contribute to understanding the mechanical behavior of the ACL in-situ, and may help tuning and validating computational knee models studying ACL function.